Становлення англійської навчальної лексикографії - Томчаковська, Юлія Олегівна; Томчаковська, Ю. О.; Томчаковская, Юлия Олеговна; Tomchakovska, Yuliia О.; Томчаковський, Олександр Георгійович; Томчаковський, О. Г.; Tomchakovskyi, Oleksandr H.; Tomchakovskyi, O. H. (My University, 2019)
Стаття присвячена дослідженню етапів становлення англійської навчальної лексикографії. Комунікативна специфіка навчальних словників полягає в їх адресованості чіткому сегменту читацької аудиторії. Це не-носії англійської мови, які вивчають її як іноземну мову і живуть поза ареалом її поширення, а, отже, поза ситуативним контекстом. Особливості користувачів, яким адресовано навчальні словники, визначають зміст і форму подачі лексикографічного матеріалу, який націлений, в першу чергу, на розширення словникового запасу читача і, крім того, має на меті ближче познайомити його з культурою англомовного соціуму. Лексикографи формулюють три проблеми, з якими стикається кожен користувач словника: як знайти потрібну інформацію; як її зрозуміти (comprehend), і як застосувати те, що ти зрозумів. Історія створення навчальних словників англійської мови починається в середині ХХ століття. Лексикографи одностайно називають такі словники як Cambridge Advanced Learner’s Dictionary, Longman Dictionary of Contemporary English, Collins COBUILD Advanced Dictionary, Oxford Advanced Learner’s Dictionary і Macmillan English Dictionary for Advanced Learners «великою п’ятіркою» навчальних словників, найвище досягнення в даній сфері лексикографічної практики (pinnacle of monolingual learners ‘dictionaries).

The article is devoted to the study of the periods of development of the English learner’s lexicography. The communicative specificity of learner’s dictionaries consists in their targeting to a clear segment of the readership. These are non-native speakers of English, studying it as a foreign language and living outside the area of its functioning, and, therefore, outside the situational context. The features of users to whom learner’s dictionaries are addressed determine the content and presentation of lexicographic material, which is aimed primarily at expanding the vocabulary of the reader and, moreover, familiarizing him more closely with the culture of English-speaking society. Lexicographers note that every user of the dictionary faces three problems: how to find the right information; how to understand it (comprehend) and how to apply what you understood. The history of the creation of educational dictionaries of the English language begins in the middle of the twentieth century. Lexicographers unanimously name such dictionaries as the Cambridge Advanced Learner’s Dictionary, Longman Dictionary of Contemporary English, Collins COBUILD Advanced Dictionary, Oxford Advanced Learner’s Dictionary and Macmillan English Dictionary for Advanced Learners as the “Big Five” of educational dictionaries, the highest achievement in this field of lexicographic practice (pinnacle of monolingual learners’ dictionaries).
Томчаковський О. Г. Становлення англійської навчальної лексикографії / О. Г. Томчаковський, Ю. О. Томчаковська // Записки романо-германської філології. – Вип. 2 (43) – 2019. – С. 252-260.
Keywords: навчальний словник; лексикографія; комунікативна специфіка; learner’s dictionary; lexicography; communicative peculiarities